2015
DOI: 10.1016/j.jot.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous spinal epidural haematoma

Abstract: SummarySpontaneous spinal epidural haematoma (SSEH) is a rare clinical condition with unknown aetiology. Prompt diagnosis and treatment are paramount because of the risk of permanent neurological deficits without appropriate intervention. We described a case of a 48-year-old man presenting with complete quadriplegia and hypoesthesia. Magnetic resonance imaging revealed cervical cord compression due to a haematoma posterior to the spinal cord. Surgical decompression and evacuation of the haematoma was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 18 publications
(19 reference statements)
2
27
0
Order By: Relevance
“…This definition also includes causes, such as a tumor, coagulopathy, vascular malformation, and cavernous angioma. 1,2,4,7 The age of patients has bimodal peaks, with an increase in the second and seventh decades. 7 Halim et al 10 demonstrated that there is no significant correlation with sex and race.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This definition also includes causes, such as a tumor, coagulopathy, vascular malformation, and cavernous angioma. 1,2,4,7 The age of patients has bimodal peaks, with an increase in the second and seventh decades. 7 Halim et al 10 demonstrated that there is no significant correlation with sex and race.…”
Section: Discussionmentioning
confidence: 99%
“…All of them presented only with minor neurologic symptoms at the examination and had rapid improvement. 1,2,4,8,10,14 Although these cases with minimal symptoms and no mass effect on the spinal cord in imaging may be managed successfully with conservative treatment, neurosurgeons should always be aware of the fact that the outcome of SSEH can be very poor when there is a mass effect and/or compression of the spinal cord. 8 In some cases, during the recovery phase of conservative treatment exacerbation of neurologic deficits may occur, which may require surgical evacuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurological status at the time of presentation has prognostic significance as patients with some residual function tend to show complete recovery. 4 Magnetic Resonance Imaging (MRI) is the diagnostic modality of choice in suspected cases of SSEH. Acute SSEH presenting within the first 24 hours of the onset of symptoms appears isointense to the cord on T1-weighted (T1W1) images and hyperintense and heterogeneous on T2 weighted (T2W1) images.…”
Section: Introductionmentioning
confidence: 99%
“…Determining clinical-stage patients has a significant prognostic value because those who have at least partial function may make a full recovery. 6,7 Proper imaging and surgical intervention should be indicated as soon as patients show clinical signs suspicious for SSEH. 7 Until now, research on SSEH has not been sufficiently established.…”
mentioning
confidence: 99%